Personality Type and its Relationship with Withdrawal Observer (Journal of the College of Education for Women, 2019)
The current research was aimed at the following:1. Measurement of Personality Type Observer of the University students.2. Identify the differences in Personality Type Observer among the University students according to variable of Sex (male / female). And according to variable of Specialization (scientific / literary)3. Measurement of Withdrawal of the University students.4. Identify the differences in Withdrawal among the University students according to variable of Sex (male / female). And according to variable of Specialization (scientific / literary).5. Identify the relationship between Personality Type Observer and Withdrawal.To achieve this aims of the research, the researchers set up the instrument is scale of Personality Type Observer that consistent (24) item and Withdrawal that consistent (20) item. And the researcher applying this scale on the sample amounted to (200) University students. Then after data processing statistically, the researchers reached the following results:1. University students have Personality Type Observer.2. There is no differences in Personality Type Observer among the University students according to variable of Sex (male / female). And There is differences according to variable of Specialization (scientific / literary) for literary3. University students have Withdrawal.4. There is no differences in Withdrawal among the University students according to variable of Sex (male / female). And There is no differences according to variable of Specialization (scientific / literary).5. There is relationship between Personality Type Observer and Withdrawal.In light of the results of this research the researchers came out with a number of recommendations and suggestions.